Adaptation for growth at various saline concentrations by the archaebacterium Methanosarcina thermophila. - Sowers, K R (1988)
We report the ability of Methanosarcina thermophila TM-1 to adapt and grow in media containing NaCl concentrations of 0.005 to 1.2 M. When adapted to marine NaCl concentrations, this species ceased to produce the heteropolysaccharide outer layer typically formed by species of nonmarine origin. concomitant with this adaptation, M. thermophila ceased to grow as multicellular aggregates and existed solely in single-cell form. The sodium ion concentration was critical for the adaptation process, although magnesium ion appeared to contribute to the cell wall stability of single cells. The results suggest that these archaebacteria possess regulatory systems that enable them to adapt to environments with a wide range of saline concentrations.